Dissipation of DDT in a heavily contaminated soil in Mato Grosso, Brazil - Dalla Villa, Ricardo [UNESP]; de Carvalho Dores, Eliana Freire Gaspar; Carbo, Leandro; Cunha, Marcelo Luiz Ferreira (Elsevier, 2006)
After the prohibition of organochlorine-pesticide use in Brazil for controlling insect vector diseases, Mato Grosso State gathered the exceeding DDT and stored it irregularly in an open air area that belongs to the National Health Foundation, causing soil contamination. This study aimed to evaluate the contamination level and dissipation of p,p′-DDT and p,p′-DDE in this area. For that, surface soil samples were collected on 19 September 2000, 15 December 2000, 4 April 2001 and soil samples 30-40 cm; 60-70 cm and 90-100 cm deep were taken from five points in the studied area on 17 July 2001. The contaminants were determined by a small scale method which consists on extraction and clean-up steps combined into one step by transferring soil samples mixed with neutral alumina to a chromatographic column prepacked with neutral alumina and elution with hexane:dichloromethane (7:3 v:v). The eluate was concentrated and the analytes were quantified by gas chromatography with an electron-capture detector. p,p′-DDT at surface soil ranged from 3800 to 7300 mg kg -1. 30-40 cm deep soil sample concentrations varied from 0.036 to 440 mg kg -1 while 90-100 cm deep samples varied from 0.069 to 180 mg kg -1. Volatilization is probably the main dissipation process. The p,p′-DDT is moving slowly downward in the soil profile, however, the levels of this contaminant are high enough to present risk to underground waters. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Contamination; Dissipation; Organochlorine; p,p′-DDT; Soil; Diseases; Extraction; Gas chromatography; Pesticides; Soils; Organochlorines; P,p′-DDT; Soil profile; Soil pollution; aluminum oxide; chlorphenotane; dichloromethane; hexane; organochlorine derivative; chemical pollutant; DDT; dissipation; gas chromatography; pesticide application; soil degradation; volatilization; Brazil; electron capture detection; extraction; risk factor; sample; soil; soil pollution; time series analysis; Environmental Monitoring; Soil Pollutants; Mato Grosso; South America; Insecta